2014
DOI: 10.1093/mnras/stu808
|View full text |Cite
|
Sign up to set email alerts
|

A new population of recently quenched elliptical galaxies in the SDSS

Abstract: We use the Sloan Digital Sky Survey to investigate the properties of massive elliptical galaxies in the local Universe (z ≤ 0.08) that have unusually blue optical colors. Through careful inspection, we distinguish elliptical from non-elliptical morphologies among a large sample of similarly blue galaxies with high central light concentrations (c r ≥ 2.6). These blue ellipticals comprise 3.7 per cent of all c r ≥ 2.6 galaxies with stellar masses between 10 10 and 10 11 h −2 M . Using published fiber spectra dia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 234 publications
(278 reference statements)
5
79
0
Order By: Relevance
“…The evolution and assembly of ellipticals is well-understood to be heterogeneous after z∼0.6 . Ellipticals that are blue and post-starburst have been found in local clusters, in a phase assumed to last 0.5 Gyr, consistent with our recent star formation event (McIntosh et al 2014). The formation of these galaxies can be explained with minor mergers, which is consistent with our imaging indicating all of the blue ellipticals have either companions or tidal debris.…”
Section: Resultssupporting
confidence: 90%
“…The evolution and assembly of ellipticals is well-understood to be heterogeneous after z∼0.6 . Ellipticals that are blue and post-starburst have been found in local clusters, in a phase assumed to last 0.5 Gyr, consistent with our recent star formation event (McIntosh et al 2014). The formation of these galaxies can be explained with minor mergers, which is consistent with our imaging indicating all of the blue ellipticals have either companions or tidal debris.…”
Section: Resultssupporting
confidence: 90%
“…Consistent with the merger origin, past observational studies of morphology and kinematics of K+A galaxies in the field hint that they are merger remnants on the way to becoming early-type galaxies (Norton et al 2001;Quintero et al 2004;Goto 2007;McIntosh et al 2014). As such, they display both early-type morphologies and signs of interactions (Schweizer 1982;Zabludoff et al 1996;Quintero et al 2004;Balogh et al 2005;Yang et al 2008;Pracy et al 2009).…”
Section: Introductionmentioning
confidence: 77%
“…The position of star-forming blue ETGs on the colour-magnitude/colour-stellar mass diagrams has been interpreted as possible migration from the red sequence to the blue cloud after acquiring sufficient fuel for star formation or fading post-starburst galaxies (Kannappan et al 2009;Huertas-Company et al 2010;Thilker et al 2010;Marino et al 2011;Moffett et al 2012;McIntosh et al 2014;Rutkowski et al 2014;Moffett et al 2015;Wong et al 2015). The sample of a few blue ETGs from other studies was found to host a significant amount of molecular gas (∼ 10 7−9 M⊙) with a linear dependence on star formation surface density within the galaxy and a higher molecular gas star formation efficiency than in normal star-forming late-type galaxies (Wei et al 2010;Stark et al 2013).…”
Section: Discussionmentioning
confidence: 99%